ERK Phosphorylation Is Not Increased in Papillary Thyroid Carcinomas with BRAFV600E Mutation Compared to That of Corresponding Normal Thyroid Tissues. (May 2012) - Kim, Sun Wook; Kim, Hee Kyung; Lee, Ji In; Jang, Hye Won; Choe, Jun-Ho; Kim, Jung-Han; Kim, Jee Soo; Hur, Kyu Yeon; Kim, Jae Hyeon; Chung, Jae Hoon
<x xml:space="preserve">Abstract</x> Background. An association between a BRAFV600E mutation and upregulation of mitogen-activated protein kinase (MAPK) pathways in human papillary thyroid carcinoma (PTC) tissues has not been demonstrated well outside of in vitro studies. The aims of this study were to evaluate the activation status of extracellular signal-regulated kinase 1/2 (ERK1/2) in human PTCs with BRAFV600E mutations compared to that of corresponding normal thyroid tissue and to determine the expressions of Raf kinase inhibitor protein (RKIP) and MAPK phosphatase 3 (MKP-3), possible regulators of ERK1/2 activation. Methods. We analyzed the presence of BRAFV600E mutation and the expressions of BRAF, total ERK, p-ERK, RKIP, and MKP-3 in 33 PTCs and corresponding normal thyroid gland tissues using western blot analysis. Results. BRAFV600E mutation was found in 28 (84.8%) of 33 PTCs, 96.4% (27/28) of which showed decreased p-ERK activity, while 75% (21/28) showed increased MKP-3 expression. There were significant differences in p-ERK and MKP-3 expressions between BRAFV600E (+) PTCs and normal thyroid glands (p < 0.001). There were no differences in expressions of BRAF, total ERK, and RKIP between PTCs and normal thyroid tissue, irrespective of the presence of BRAFV600E mutation. Conclusions. In human BRAFV600E (+) PTCs, ERK phosphorylation is decreased compared to normal thyroid glands and the observed decrease in ERK1/2 MAPK phosphorylation in BRAFV600E (+) PTCs may be associated with increased MKP-3 activity.